Treatment of hip fractures in the elderly with the “TriboFit” System: retrospective review of our experience - Molinari, Giampaolo; Galmarini, Valter; Ferrara, Fabrizio; Capelli, Roberto Maria (Lo Scalpello - Journal, 2021)
Background. We assessed the TriboFit Hip System, an acetabular “buffer” useful in surgical treatment of medial femoral neck fractures in elderly patients in which a hemiarthroplasty was implanted instead of a total hip arthroplasty. It consists of a gelatinous-plastic buffer made of polycarbonate urethane. Methods. Between 2008 and 2011, 38 patients with medial femoral neck fracture were operated on by a single surgeon, 19 of whom were clinically and radiographically evaluated with a mean follow-up of 18 months. From 2012 to 2016, 9 patients from the first review and two new cases were re-evaluated. Results. Radiographic imaging showed good quality of the peri-prosthetic bone in all cases in 2008-2011, without osteolysis. The Harris Hip Score was excellent and good in 79% of cases. In the subsequent review, we observed a reduction of the positive results. Conclusions. The beginning of our experience was completely positive for good results in the short term, as in most of the scarce literature on the subject. However, after the second review, we decided to abandon the use of TriboFit Hip System, given that the results not as positive as before.